Three novels against neoliberalism: "El traductor", "El trabajo" y "La intemperie" - Vitagliano, Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The article proposes to analyze the connections between the spread of neoliberalism in Argentina during the 90s and the construction of the rhetoric of a new realism through three novels: El Traductor (1998) by Salvador Benesdra, El trabajo (2007) by Anibal Jarkowski and La intemperie (2008) by Gabriela Massuh. The impact that produced the neoliberal policies in society had a turnover also known modes of relationship literature and social reality, opening to an exploration of aesthetic possibilities that have defined the plurality of poetics that we recognize nowadays in the contemporary novel in the country.
Keywords: Argentine novel; Neoliberalism; Rhetoric; Realism; Aesthetics